Bibliometric Analysis of Financial Inclusion Research - Judijanto, Loso; Supriadi, Adih (West Science Accounting and Finance, 2025)
Financial inclusion has emerged as a crucial factor in promoting economic development, reducing poverty, and fostering financial stability. This study employs a bibliometric analysis to explore the intellectual landscape, key research themes, and trends in financial inclusion research using data exclusively from the Scopus database. Utilizing VOSviewer, the study examines keyword co-occurrence, co-authorship networks, and geographic distribution to identify influential scholars, institutions, and countries contributing to the field. The findings reveal an evolution from traditional microfinance approaches toward digital financial services, financial technology (FinTech), and sustainability-linked financial inclusion initiatives. The analysis highlights strong international research collaborations, with India, China, and the United Kingdom playing significant roles in shaping financial inclusion discourse. Moreover, emerging research trends suggest an increasing focus on digital finance, environmental sustainability, and gender disparities in financial access. Despite progress, persistent challenges such as financial literacy gaps, regulatory barriers, and regional inequalities remain critical concerns. This study contributes to the understanding of financial inclusion research trends and provides insights for policymakers, financial institutions, and researchers to design more inclusive and effective financial policies. Future research should integrate interdisciplinary approaches and advanced data analytics to address existing gaps and enhance financial accessibility globally.